Pengembangan Media Pembelajaran Pendidikan Agama Islam Berbasis Audio Visual Terintegrasi Kearifan Lokal Di Sekolah Dasar - Ariska Ariska (Institut Agama Islam Negeri Palopo, 2020)
The purpose of this scientific essay is 1) to find out how the media development of the procedure of ablution is an audio-based visual process integrated local wisdom in the grade II students of SDN 161 Lampuawa Regency of North Luwu. 2) to know how Kevaliand Media Learning Ordinance ablution Audio-based visual process integrated local wisdom. 3) to find out how the effectiveness of learning procedures of ablution-based audio visuals integrated local wisdom. This research method uses Research & Development to develop products using 4-D development model consisting of four phases: define, design, develop, and disseminate. In research conducted three stages, namely to develop because of limited time and cost. The test subject is a grade II student totalling 28 students. Data collection techniques used validation sheets, interviews, field note sheets. Analysis of the data used to test its valid using Aiken's formula. Based on the results of the analysis obtained the validity of learning media for 0.78 included in the valid and effective category. The effectiveness of learning media is based on the results of field notes during the learning process that the researchers have had that students respond well to learning using developed media.